The Moral Dilemma: Between Tax Ethics and the Temptation of Evasion - Santoso, Budi; Nisrina, Ulfah Laila; Srimiatun, Srimiatun (Fakultas Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2024)
This study aims to determine the effect of tax justice, taxation system and tax discrimination on tax evasion. The population in this study is an individual taxpayer who is registered at Kantor Pelayanan Pajak Pratama Makassar Utara. The sampling technique used purposive sampling method. The respondents of this study were 100 respondents. Collecting data using a questionnaire method. The analysis method uses multiple linear regression with the help of SPSS version 25 program. The results show that tax justice has a significant negative effect on tax evasion, the taxation system has no negative effect on tax evasion and tax discrimination has a significant positive effect on tax evasion.